Pengaruh Pembelajaran Akuntansi, Literasi Keuangan dan Kontrol Diri terhadap Perilaku Keuangan Mahasiswa Akuntansi - Yatiningsih, Ana; boedi, Soelistijono; Ruwanti, Gemi; Kadir, Abdul (Owner : Riset dan Jurnal Akuntansi, 2024)
Financial behavior is the actions a person takes in processing, managing and using financial from existing sources. Individuals who have financial behavior tend to have an effective attitude in using the finances they obtain. Someone who is good at financial management, the process of managing financial expenses and income as well as using financial resources from existing resources. Therefore this research aims to determine the influence of accounting learning, financial literacy and self-control on the financial behavior of individual students majoring in accounting at universities in Banjarmasin. The population in this study were students majoring in accounting from several universities in the city of Banjarmasin, especially STIE Indonesia Banjarmasin, STIE Nasional, STIE Pancasetia and Lambung Mangkurat university. The sampling technique in this research used purposive sampling. The number of samples obtained was 100 respondents. The data collection technique used was a questionnaire. This research uses mulitiple linear regression analiysis. The results of the research show that the variabels of accounting learning and financial literacy have a positive and significant effect on the individual financial behavior of students majoring in accounting at universities in Banjarmasin, while self-control has no effect on individual financial behavior of students majoring in accounting at a university in Banjarmasin.